Comparison between Ankle Stretching and Self Massage for Plantar Fascia Treatments on Male and Female Posture Balance - J Jayadi; Mohammad Furqon Hidayatulah; Noer Rachma (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
When performing physical activity and sports, men and women are at risk of the plantar fascia that could decrease foot functions when walking, running, and jumping. Thus it requires accurate prediction results in handling it. This study aimed to determine whether clinical findings can help plantar fascia flexibility treatments and managements through ankle stretching and self-massage interventions on posture balance based on gender. This study used a quasi-experimental design with a 2x2 factorial design for male and female categories. The population of this study was 300 students, while the samples were 40 students aged 19-26 years, consisting of 20 males and 20 females. The sampling technique used stratified random sampling. Furthermore, the ankle dorsiflexion intervention was performed by stretching the ankle to overcome plantar stiffness. For self-massage, the golf ball roll relaxation gave a relaxing effect on plantar pressure. The ankle dorsiflexion and golf ball roll relaxation were performed for 45 seconds. The data collection instrument of this study was a standing stork test as a measurement reference. Data analysis used two-way ANOVA statistical test with the help of SPSS application. The results showed that the significance value of comparing ankle stretching and self-massage technique effects for plantar fascia on the posture balance based on gender was (p0.05). The significance value of posture balance in terms of gender was (p) = 0.417. Meanwhile, the difference between ankle stretching and self-massage interaction based on gender was (p) = 0.000. This study indicates that these findings can assist the treatment and management of plantar fascia flexibility through ankle stretching and self-massage interventions to balance the posture in terms of gender. Treatment for plantar fascia flexibility is more effective with ankle stretching.